PROFIL PEMAHAMAN KONSEP MATEMATIKA BENTUK ALJABAR PADA SISWA DENGAN GAYA BELAJAR KOGNITIF FIELD INDEPENDENT - Mina Tika Selviana; Sugiyanti Yayan; Agnita Siska Pramasdyahsari (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2021)
Mathematical understanding is the process of placing knowledge that is being studied and then relating it to the knowledge that students already have. This study aims to determine the profile of understanding the mathematical concept of algebra in terms of field independent cognitive style. This is a descriptive qualitative research. The subjects taken were seventh grade students at a State Junior High School in Semarang in the 2nd semester of the 2020/2021 academic year who had a field independent cognitive style. Data collection was carried out by GEFT test, mathematical concept understanding test, and interviews. The data analysis technique was carried out in 3 stages, namely data reduction, data presentation, and conclusion drawing, then a triangulation method was carried out. The results of the analysis shows that the fulfillment of all indicators of understanding mathematical concepts to the maximum is indicated by students being able to answer all questions that contain indicators of understanding mathematical concepts. Subjects with field independent cognitive style have a good ability to understand the concept of algebraic forms.